Aksara-Aksara Penyimpan Informasi di Banten - Pudjiastuti, Titik (UI Scholars Hub, 2016)
Banten is one of the 34 provinces which helped to establish the Republic of Indonesia. Although it was just acknowledged as a province of Indonesia in 2000, as a pepper producer Banten had been known around the world long before its sultanate even existed. The various written sources consist of scripts, archives, and inscriptions from various backgrounds, such as history, literature, and religion. This research found that there are several scripts used as a written medium in Banten, such as Arabic, Jawi (Malay-Arabic), Pegon (Arabic-Javanese), Hanacaraka, and Latin. From the text content point of view, it has been found that these scripts also function as an information depositor of Banten.